2018
DOI: 10.1021/acscatal.7b04466
|View full text |Cite
|
Sign up to set email alerts
|

Climbing the Volcano of Electrocatalytic Activity while Avoiding Catalyst Corrosion: Ni3P, a Hydrogen Evolution Electrocatalyst Stable in Both Acid and Alkali

Abstract: We report microcrystalline Ni3P as a noble-metal-free electrocatalyst for the H2 evolution reaction (HER) with high activity just below those of Ni5P4 and Pt, the two most efficient HER catalysts known. Ni3P has previously been dismissed for the HER, owing to its anticipated corrosion and its low activity when formed as an impurity in amorphous alloys. We observe higher activity of single-phase Ni3P crystallites than for other nickel phosphides (except Ni5P4) in acid, high corrosion tolerance in acid, and zero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
161
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(173 citation statements)
references
References 62 publications
7
161
0
Order By: Relevance
“…The Ni-P alloy deposit was largely amorphous, displaying only a weak, broad peak centered on the (111) facet of fcc nickel (ICDD reference pattern 04-010-6148), similar to previous literature reports for highphosphorus-content, electroless nickel deposits [37]. Additionally, this provides strong evidence against the formation of metal phosphides like Ni3P, which have also shown electrocatalytic HER activity [38]. In contrast, the deposited platinum nanoislands were crystalline in nature, as seen by the appearance of fcc platinum (ICDD reference pattern 04-001-0112) with higher platinum loadings (Figure 3a).…”
Section: Physical Characterizationsupporting
confidence: 87%
“…The Ni-P alloy deposit was largely amorphous, displaying only a weak, broad peak centered on the (111) facet of fcc nickel (ICDD reference pattern 04-010-6148), similar to previous literature reports for highphosphorus-content, electroless nickel deposits [37]. Additionally, this provides strong evidence against the formation of metal phosphides like Ni3P, which have also shown electrocatalytic HER activity [38]. In contrast, the deposited platinum nanoislands were crystalline in nature, as seen by the appearance of fcc platinum (ICDD reference pattern 04-001-0112) with higher platinum loadings (Figure 3a).…”
Section: Physical Characterizationsupporting
confidence: 87%
“…The referenced commercial Pt/C sample gives the smallest slope of 37 mV/dec, followed by P-Mo-N of 43 mV/dec, Mo-N of 76 mV/dec, and Mo 2 N-r of 71 mV/dec. A slope larger than 30 mV/dec for the P-Mo-N sample suggests a Volmer-Heyrovsky route for HER, 10,11,14 . The exchange current density (j 0 ), the most inherent measure of HER activity, was also calculated based on the Tafel equations (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 92%
“…H ydrogen evolution reaction (HER) from electrocatalytic water splitting has been regarded as one of the important strategies to solve the world's increasing energy and environment issues [1][2][3][4][5][6][7][8][9][10] . Water electrolysis requires a stable electrocatalyst which has the ability to overcome high overpotential and provide efficient activity.…”
mentioning
confidence: 99%
“…Notably, nickel phosphides have eight mono-phosphides and poly-phosphides with different Ni/P ratios, i.e., Ni3P, Ni5P2, Ni12P5, Ni2P, Ni5P4, NiP, NiP2, and NiP3, and the stoichiometric compositions, crystal phases, and crystal facets show influences on the electrocatalytic HER activity. The nickel phosphides of Ni2P [45], Ni5P4 [46], Ni12P5 [47], Ni3P [48], and NiP2 [49] phases are generally obtained according to the reported results. Pan et al investigated the HER performance of different types of nickel phosphides (Ni12P5, Ni2P, and Ni5P4) and found that their catalytic performance followed the order of Ni5P4>Ni2P>Ni12P5 [50].…”
Section: Properties Of Nickel Phosphidesmentioning
confidence: 75%
“…The SEM images in Figure 9c Figure 9f and Tafel plots in Figure 9g clearly show that the HER performance of nickel phosphide nanosheets prepared by S B-U method is better than the one prepared by the S F-B method. Alternatively, Laursen et al prepared Ni 3 P microparticles by a conventional solid-state reaction, which allowed Ni (s) and P (s) to react in an evacuated quartz tube at 700 • C for 24 h [48]. The microcrystalline Ni 3 P as a noble-metal-free electrocatalyst for HER shows high activity lower than those of Ni 5 P 4 and Pt, which are the two most efficient HER catalysts known.…”
Section: Thermal Phosphidation With Red Phosphorusmentioning
confidence: 99%